Participatory Dialogue for Social Change in Fisheries Community: Comparing Catalysts in Kawali and Bangsring Villages - Asy Khofsah; Sarwititi Sarwoprasodjo; Siti Amanah (Lembaga Bale Literasi, 2026)
Poverty in marine and fisheries communities remains a major challenge in rural development in Indonesia. This study analyzes the role of participatory communication in the Smart Fisheries Village (SFV) as an community development program using the Communication for Social Change (CFSC) framework, focusing on dialogue catalysts and participatory dialogue processes. A mixed methods explanatory sequential design was applied through surveys of 170 respondents and in-depth interviews with 28 informants in Kawali and Bangsring Villages. Results show that government support was the main catalyst in Kawali, while leadership communication was main catalyst in Bangsring. Participatory dialogue was strong at the internal community level but weakened in strategic decision-making involving external actors. The study reveals a participation paradox, high involvement does not necessarily lead to equal access to power, authority, and strategic decision-making.